Growth of micro-ikebana on a floating substrate: a method to monitor local supersaturation levels. Issue 10 (13th February 2015) - Fischer, V.; Karthaus, O.
Abstract : The growth of biomimetic SrCO3 –SiO2 micro-ikebana was conducted by an organic additive-free process to monitor the degree of local supersaturation at the surface of a floating substrate. The obtained crystallization pattern mirrors the level of local concentration which was the basis to derive a mathematical equation for the prediction of local nucleation rates. Abstract : Small changes make a big difference: we demonstrate how slight changes in the supersaturation have a huge impact on the formed crystal morphology and present a convenient method to monitor the level of local supersaturation on a flat substrate. Further we provide a non-additive based explanation for natural biomineralization processes.